MOTIVASI RUSIA MEMBANTU KELOMPOK OPOSISI DALAM PENGGULINGAN PRESIDEN KYRGIZTAN TAHUN 2010 - Sholihat, Irhamnah Muslimah; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research will describes about motivation Russian help opposition group inKyrgiztan’s president Coup in 2010. Kyrgyztan is strategic country in Central Asia,which is have two military bases. There are Manas air base and Kant air base.Manas air base is US own that established in 2001 after WTC Tragedy to responsethe terrorist isuued for security. Manas air base is making Russian government indilemmatic sutuation. Russian worried their hegemony will disturbed, and take theresponse of the US action with build the base in Kant. This research shows that animportant point which becomes references is describing the same interest betweenRussian government and opposition group of Kyrgyztan in ouster the Bakiyev fromKyrgyztan. The same interest is minimalize US influence in Kyrgyztan by ouster theBakiyev which is Bakiyev is pro US. Most of the decision that Bakiyev is taken just forgetting the interest for their.Keywords: Coup, Hegemony, National Interest, Security.